THE DEVELOPMENT AND ANALYSIS OF ECO-PRINT AND SCREEN PRINTING COMBINATION USING NATURAL DYES - TRI, YULIANA; NOORYAN, BAHARI (Fibres and Textiles, 2023)
Natural dye is one of the solutions to alleviate environmental damage caused by the textile industry. Existing synthetic dyes have been proven to adversely affect the environment and human. Hence, revisiting natural dyes becomes a correct decision to alleviate existing environmental problems. Eco-print is one of the natural dyeing methods done by using plants typically found in the surroundings. This method has become the subject of various developments, both in its mordanting and making processes. Its visual aesthetics should also receive attention to avoid stagnation. Further development and innovation are necessary. The purpose of this study was to develop the visual aesthetic aspect of the eco-print method. It particularly focused on developing the design and production technique in terms of concepts, materials, and working techniques. This work also adopted a screen printing technique to enrich the motifs and colors. The method utilized in this research was art-based research with the premise of adapting artistic creativity to social research using an artistic practice approach because both are holistic and dynamic. The result showed that eco-print and screen printing methods could be combined, as the latter significantly enhance the eco-print product’s visual aesthetics. However, the result of this combination exhibited poor color fastness, implying the need for further study.